Spatio-temporal Variations in Water Quality, Chlorophyll-a Content and Benthic Macroinvertebrates in the Tengragiri Mangrove Estuary at the Barguna Coastal Region, Bangladesh (Journal of the Bangladesh Agricultural University, 2025)
The study was conducted to assess the spatio-temporal fluctuations of water quality parameters, Chlorophyll a contents and benthic macroinvertebrates in the Tengragiri mangrove estuary, Barguna coastal region. Water samples were collected from five sampling stations to analyze the temperature, transparency, electrical conductivity, total dissolved solids, pH, dissolved oxygen, biological oxygen demand, total hardness, total alkalinity, ammonium, sulphate, phosphate, nitrate, and Chlorophyll-a. Water quality parameters were analyzed in the laboratory of the Department of Environmental Science and Resource Management of the Mawlana Bhashani Science and Technology University (MBSTU) following the respective standard procedures. The results indicated that the temperature varied from 21.58 to 31.02° C, transparency 5.58 to 30.48 cm, EC 46.20 to 310.40  , TDS 204.33 to 1977 mg/L, pH 5.45 to 6.51, DO 7.27 to 7.70 mg/L, BOD 1.20 to 2.50 mg/L, total hardness 126 to 215.33 mg/L, and total alkalinity 93.77 to 166.18 mg/L. The nutrients were found ammonium 0.56 to 1.74 mg/L, sulphate 27.84 to 51.72 mg/L, phosphate 0.60 to 1.97 mg/L, nitrate 2.44 to 7.69 mg/L, and Chlorophyll a 0.42 to 1.45 μg/L. The study indicated that TH, TA, phosphate, nitrate and ammonium exceeded the recommended level for aquatic environment. On the other hand, temperature, TDS, BOD, EC, sulphate, and Chlorophyll a were within the standard level for aquatic environment. Fourteen species of macro benthos were identified over the two sampling seasons. The peak benthos abundance (8 to 12) occurred during the wet season, attributed to superior water quality. Simpson’s biodiversity index revealed that the benthic diversity status was high (0.916). The results demonstrated that the Tengragiri mangrove estuarine ecosystem was in a healthy state, which may be maintained via consistent monitoring and management.J Bangladesh Agril Univ 23(3): 442–454, 2025